2009
DOI: 10.3749/canmin.47.3.663
|View full text |Cite
|
Sign up to set email alerts
|

RAMAN AND IR SPECTROSCOPIC STUDIES OF ALUNITE-SUPERGROUP COMPOUNDS CONTAINING Al, Cr3+, Fe3+ AND V3+ AT THE B SITE

Abstract: Raman and IR spectroscopies, X-ray diffraction and chemical analysis have been used to characterize synthetic compounds of the alunite supergroup of formula AB 3 (SO 4 ) 2 (OH) 6 , with A = Na + , K + , H 3 O + and B = Al, Cr 3+ , Fe 3+ , V 3+ . For each A-site cation, the proportion of B-site vacancies decreases in the same order as the effective ionic radius of the B-site cations (Al > Cr > Fe > V). Raman and IR spectra of the compounds with B = Al and Fe 3+ (alunite-and jarosite-group phases) show very clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 44 publications
2
14
0
1
Order By: Relevance
“…The peaks compare well with literature [9,15,27,28], where the sulphate bands are found between 940 and 1300 cm −1 . The main differences between the alunite to jarosite spectrum are that the sulphate band is shifted to higher wavenumbers, as are the bands in the 400-700 cm −1 region.…”
Section: Vibrational Sepctroscopysupporting
confidence: 88%
See 3 more Smart Citations
“…The peaks compare well with literature [9,15,27,28], where the sulphate bands are found between 940 and 1300 cm −1 . The main differences between the alunite to jarosite spectrum are that the sulphate band is shifted to higher wavenumbers, as are the bands in the 400-700 cm −1 region.…”
Section: Vibrational Sepctroscopysupporting
confidence: 88%
“…The calculated compositions are shown in Table 2. The values for Fe, K and Al were all within expected ranges [9,14]. These results showed that Al substitution above 20% did not occur until the initial solution Al/(Al + Fe) content had increased above 0.9.…”
Section: Elemental Analysissupporting
confidence: 57%
See 2 more Smart Citations
“…The alunite structure often contains A-and Bsite vacancies (Dutrizac and Jambor 2000;Greedan 2001), and "excess", non-OH water, which is assumed to be in the form of hydronium (or "oxonium," H 3 O + ) that substitutes for K + on the A site (Ripmeester et al 1986;Alpers et al 1989). As Lager et al (2001) point out, the existence of hydronium is supported by K + deficiencies in the structure and the fact that hydronium alunite end-members without any alkalis can be synthesized (Murphy et al 2009). …”
Section: Introductionmentioning
confidence: 99%